Strategies for Utilizing Technology in Learning - Abbas, Azwar; Nurjannah, Asfinatu; Isnaini, Rahma; Eliyana, Ema (Mutiara Intelektual Indonesia Press, 2024)
This study investigates the intercultural relationship development of English as a Foreign Language (EFL) students participating in an International Learning Program. Amid travel restrictions, a limited number of students engaged in a cross-border experience in Malaysia and Singapore. Employing a descriptive qualitative approach, the research examines the stages of intercultural relationship development and associated challenges. Twenty eighth-grade students from East Java, Indonesia, comprising an equal distribution of male and female participants, were selected for the study. Through analysis, three distinctive stages emerged in the process of intercultural competence (ICC) development: